Influence of Different Wax Hardening Agents on Surface Roughness of Refractory Cast Investment Materials - Zahraa Noori Yassen; Israa Mohammed Hummudi (Journal of Techniques)
Background: Phosphate-bonded investments produce a refractory cast model with rough surface and undesirable properties. Dental Surface hardening agents are then applied to refractory investment materials to enhance its properties.